Competitive insertion of the citrus-lemon chain in global value chains in Colombia - López, Alexander Blandón; Rubio-Rodríguez, Gustavo Adolfo; Vega, Gerardo Pedraza (Zielona Góra: Faculty of Economics and Management Press)
This research delves into the identification of opportunities for the consolidation of the lemon value chain in the department of Tolima, Colombia, through the associativity model called: Special Administrative Planning Region. This model is a land-use planning system, officially recognized in Article 325 of the Political Constitution of Colombia and in Law 114 of 2011, which functions as a planning tool at the regional level.
Keywords: Global Value Chain; Inclusion; Regional Competitiveness; Lemon